EVALUATION OF BUSINESS PROCESS AND UNDERSTANDING OF FINANCIAL LITERACY IN FISH CULTIVATOR GROUP - Masnila, Nelly; Mayasari, Riana; Isa, Indra Griha Tofik; Hendradinata, Hendradinata (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The specific purpose of this research is to know the business process of fish farming and to find out the problems and opportunities to produce Appropriate Technology (TTG) in fish farming with IoT. Data collection techniques used were observation, literature study and interviews. The data validity test was carried out before data analysis with credibility test through Triangulation, Member Check, and negative case analysis techniques. Data analysis used thematic analysis. The coding technique used was divided into three, namely: open coding, axial coding, and selective coding. The problems in business processes and understanding of financial literacy are the inability of human resources.